Feasibility Analysis of the Development of the Kepok Banana Flour Industry and Opportunities for Improving Farmer Welfare in Mentawai Islands, West Sumatera - Istiqlaliyah Muflikhati; Pudji Muljono; Qodarian Pramukanto; Agief Julio Pratama; M.A. Zaim Adzkiya (Jurnal Mamangan, 2025)
Banana cultivation particularly Kepok bananas, plays a significant role as a commercial commodity in the Mentawai Islands Regency. This study aims to assess the developing a banana flour processing industry in the region by analyzing the commodity's potential, determining suitable locations, and evaluating industrial feasibility.   The approach method for the feasibility study of the banana flour industry consists of 1) analysis of the potential of banana commodities in the Mentawai Islands Regency, 2) determination of the location of the banana flour processing industry, 3) feasibility study of the banana flour agro-industry, and 4) recommendations for the feasibility of the banana flour industry in the Mentawai Islands Regency. The research was carried out from May to November 2024.  The data collected includes primary data and secondary data.  Several questionnaires were used in the data collection process, including other questionnaires for farmers (62 persons), extension workers (12 persons), trader collectors (6 persons), and stakeholders (representation from 15 institutions). The data obtained were then analyzed using several analyses, including analysis of the current condition of banana farming management, business sustainability analysis,  and SWOT analysis. The findings indicate that Kepok banana cultivation in the region is highly favorable, supported by suitable agronomic conditions. Furthermore, the feasibility assessment demonstrates the potential for success across agronomy, technology, processing, management, socio-economic benefits, and administrative aspects. Establishing a banana flour processing industry is expected to optimize the use of local banana resources and generate economic benefits. It is anticipated that these initiatives will not only enhance the efficiency of banana utilization but also improve the welfare of banana farming families in the Mentawai Islands Regency. This study emphasizes the strategic importance of agro-industrial development in empowering rural communities.